2004
DOI: 10.1023/b:boli.0000042984.42433.d8
|View full text |Cite
|
Sign up to set email alerts
|

Congenital disorder of glycosylation (CDG) type Ie. A new patient

Abstract: CDG Ie is caused by a deficiency of dolichol-phosphate-mannose synthase 1 (DPM1), an enzyme involved in N-glycan assembly in the endoplasmic reticulum. Three proteins are known to be part of the synthase complex: DPM 1, DPM2 and DPM3. Only mutations in DPM1, the catalytic subunit, have been described in three families. One was homozygous for the c274C>G (R92G) mutation in DPM1 and two others were compound heterozygous for R92G and a c628delC deletion or a c331-343del13, respectively. Clinical features were a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 7 publications
4
34
0
Order By: Relevance
“…In addition to the misfolded hypoglycosylated proteins unable to leave the ER, the accumulation of free and truncated LLO might contribute towards ER stress [11]. LLO analysis of DPM1-CDG cells by other authors [27] showed an accumulation of the truncated LLO form. In PMM2-CDG patient-derived fibroblasts, the ER stress observed might be caused by a subphysiological glucose concentration that induces the accumulation of LLO intermediates [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the misfolded hypoglycosylated proteins unable to leave the ER, the accumulation of free and truncated LLO might contribute towards ER stress [11]. LLO analysis of DPM1-CDG cells by other authors [27] showed an accumulation of the truncated LLO form. In PMM2-CDG patient-derived fibroblasts, the ER stress observed might be caused by a subphysiological glucose concentration that induces the accumulation of LLO intermediates [28].…”
Section: Discussionmentioning
confidence: 99%
“…Visual abnormalities are described in patients with CDG-Id (MIM 601110), including optic nerve atrophy,57 coloboma of the iris,5 strabismus, and severe visual impairment with abnormal electroretinography 8 9. In CDG-Ie (MIM 601799) patients cortical blindness, esotropia, nystagmus and optic nerve atrophy have been reported 10 11. Optic nerve atrophy,12 horizontal nystagmus, divergent strabismus, lack of visual fixation and amaurosis have been observed in CDG-If (MIM 609180) 13.…”
mentioning
confidence: 99%
“…The clinical pictures of the five patients identified to date (8) are most frequently characterized by developmental delay and severe neurologic problems, among which seizures and acquired microcephaly are prominent. In cells from the patients, the Dol-P-Man synthase activity is severely diminished.…”
mentioning
confidence: 99%